Causality Analysis of Construction Failure Using The Event Tree Analysis Method and Fault Tree Analysis - Ambartiyas, Puspita; Bhaskara, Adwitya (Rekayasa Sipil, 2025)
A Hotel Apartment project had to be halted, leaving the existing building abandoned for several years. The adverse impacts of abandoned buildings can be structural, physical, environmental, aesthetic, health, economic, reputational, and ecological. Abandoned buildings with unknown structural strength are very vulnerable to disasters and can be dangerous if they collapse. This research was conducted to analyze the causality of construction failure in an Apartment Hotel that has been abandoned for the past 6 years using the Event Tree Analysis (ETA) and Fault Tree Analysis (FTA) methods. The study aimed to determine the probability and causes of construction failures and identify the associated risks. Visually, the building experienced some damage to some of the structural components that had been built. The results of the Rapid Visual Screening analysis show that the building has damage to the components of the existing structural elements with a percentage of 43.67% and is included in the Moderate Damage damage level category. Based on the RVS results, an evaluation is carried out using Event Tree Analysis and Fault Tree Analysis to determine the causal flow of construction failure scenarios and the causes of construction failure.